Head‐to‐head comparison of [18F]Flortaucipir and amyloid PET visual reads for differential diagnosis: An international, multi‐center study. (December 2021) - Soleimani‐Meigooni, David N.; Smith, Ruben; Provost, Karine; Lesman‐Segev, Orit H.; Cho, Hanna; Edwards, Lauren; Iaccarino, Leonardo; La Joie, Renaud; Ossenkoppele, Rik; Strandberg, Olof; Strom, Amelia; Lyoo, Chul Hyoung; et al.
Abstract: Background: Quantitative [ 18 F]Flortaucipir (FTP) tau PET analysis has good discriminative accuracy for Alzheimer's disease (AD), but visual reads are used clinically. We aimed to compare the diagnostic accuracy of FTP‐PET to amyloid PET visual reads for distinguishing AD dementia and amyloid‐positive mild cognitive impairment (MCI) from other neurodegenerative diseases and cognitively normal (CN) controls. Method: We included 661 participants studied with FTP and amyloid PET at UCSF, Lund University, and Gangnam Severance Hospital (Table 1). Amyloid PET tracers were site‐specific (UCSF, [ 11 C]PIB; Lund, [ 18 F]Flutemetamol; Gangnam, [ 18 F]Florbetaben). Three visual raters interpreted amyloid PET using tracer‐specific criteria and FTP‐PET using a recently proposed method (Figure 1; Sonni et al . Alzheimer's Dement . 2020, 12:e12133. doi: 10.1002/dad2.12133). Amyloid and FTP‐PET were read in separate, randomized batches, blinded to the reads of the other physicians. The majority interpretation of each scan as amyloid positive/negative and tau positive/negative was used in the primary analysis. Diagnostic performance of FTP and amyloid PET visual reads, including sensitivity and specificity, were calculated. Kappa statistics for intra‐ and inter‐rater reliability were calculated. Result: Amyloid and FTP‐PET visual reads had similar sensitivity (92.6%, 95%‐confidence interval [88.7‐95.5%], 92.2% [88.2‐95.2%], respectively) and specificity (82.9% [78.9‐86.5%], 78.2% [73.9‐82.1%], respectively) for distinguishing AD and amyloid‐positive MCI from all other dementias and CN controls (Table 2). Amyloid PET and FTP‐PET visual reads had similar diagnostic performance for distinguishing AD or amyloid‐positive MCI from non‐AD neurodegenerative disorders or CN controls (Table 3). FTP‐PET intra‐rater reliability ranged from κ=0.80‐1.00 (p<0.0001), and inter‐rater reliability between reader pairs ranged from κ=0.78‐0.85 (p<0.0001). Amyloid PET intra‐rater reliability was κ=0.97 (p<0.0001) for each reader, and inter‐rater reliability between reader pairs ranged from κ=0.82‐0.88 (p<0.0001). Conclusion: FTP and amyloid PET visual reads have similar diagnostic performance and high intra‐ and inter‐rater reliability. Further analysis will be performed to determine if patient characteristics can predict when one PET modality will outperform the other for AD diagnosis.